Ammonium ion intercalated hydrated vanadium pentoxide for advanced aqueous rechargeable Zn-ion batteries. (December 2020) - Xu, L.; Zhang, Y.; Zheng, J.; Jiang, H.; Hu, T.; Meng, C.
Abstract: Considering many factors, including environmental protection, high cost, and limited resource, aqueous rechargeable Zn-ion batteries (ARZIBs) are expected to be a new next-generation grid to replace Li-ion batteries. The open layered framework of (metal ions intercalated) hydrated vanadium pentoxides is conducive to the transfer and diffusion of zinc ions, making this kind of material a promising cathode material. In this work, ammonium ion (NH4 + ) intercalated hydrated vanadium pentoxide [(NH4 )x V2 O5 ·nH2 O, abbreviated as NVOH] is prepared by a comparatively low-temperature synthesis and developed as a cathode material for ARZIBs. The influence of different types and concentrations of zinc salt electrolytes on the electrochemical performance is first studied, demonstrating that 3 M Zn(CF3 SO3 )2 shows the most excellent performance. The Zn//NVOH battery delivers superior electrochemical reversibility, a high specific capacity (372 mAh·g -1 at 0.1 A·g -1 ), a preeminent energy density (273 Wh·kg -1 at 155 W·kg -1 ), and a long lifespan cycling performance (175 mAh·g -1 after 2, 000 cycles at 5 A·g -1 ), which is superior to or comparable to most up-to-the-minute V-based materials applied to ARZIBs. The intercalation reversibility of zinc ion is proved during the electrochemical reaction by various characteristic measurements. This work not only provides a low-temperature hydrothermal synthesis route (100 °C) for NVOH but also demonstrates that it can be a promising supplement for zinc ion batteries or other portable battery devices. Graphical abstract: Image 1 Highlights: NVOH is prepared by a comparatively low-temperature synthesis (100 °C) applied to ARZIBs. The influence of zinc salt electrolytes on the electrochemical performance is studied. The Zn//NVOH battery delivers a specific capacity of 372 mAh g −1 at 0.1 A g −1 ), an energy density of 273 Wh kg −1 at 155 W kg −1 . The Zn//NVOH battery shows a long lifespan cycling performance.